Q-switched Erbium-doped fiber laser using MoSe 2 as saturable absorber - Ahmad, Harith; Suthaskumar, M.; Tiu, Zian Cheak; Zarei, A.; Harun, Sulaiman Wadi (Elsevier, 2016)
A Q-switched Erbium-doped fiber laser by using MoSe2 thin film as saturable absorber is experimentally demonstrated. The bulk MoSe2 is processed into few layer MoSe2 based on liquid phase exfoliation technique, and further fabricated into thin film by using polyvinyl alcohol polymer. Q-switching operation is obtained from pump power range of 22.4–102.0 mW. The pulse repetition rate shows an increasing trend from 16.9 kHz to 32.8 kHz, whereas the pulse width exhibits a decreasing trend from 59.1 μs to 30.4 μs. The highest pulse energy of 57.9 nJ is obtained at pump power of 102.0 mW.